2014
DOI: 10.1073/pnas.1421131111
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-dependent contributions of visual orientation cues in parietal cortex

Abstract: Creating accurate 3D representations of the world from 2D retinal images is a fundamental task for the visual system. However, the reliability of different 3D visual signals depends inherently on viewing geometry, such as how much an object is slanted in depth. Human perceptual studies have correspondingly shown that texture and binocular disparity cues for object orientation are combined according to their slant-dependent reliabilities. Where and how this cue combination occurs in the brain is currently unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
2
26
1
Order By: Relevance
“…Two male rhesus monkeys ( Macaca mulatta ) participated (Monkey L: 5 years of age, ~7.8 kg in weight; Monkey F: 4 years of age, ~5.5 kg in weight). A Delrin ring for stabilizing the head during training and experimental sessions was attached to the skull under general anesthesia [32, 38, 39]. After recovery, each monkey was trained to sit in a custom primate chair with head restraint, and to fixate a visual target within 2° version and 1° vergence windows for a liquid reward.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two male rhesus monkeys ( Macaca mulatta ) participated (Monkey L: 5 years of age, ~7.8 kg in weight; Monkey F: 4 years of age, ~5.5 kg in weight). A Delrin ring for stabilizing the head during training and experimental sessions was attached to the skull under general anesthesia [32, 38, 39]. After recovery, each monkey was trained to sit in a custom primate chair with head restraint, and to fixate a visual target within 2° version and 1° vergence windows for a liquid reward.…”
Section: Methodsmentioning
confidence: 99%
“…Under natural viewing conditions, changes in slant or distance affect the retinotopic area subtended by an object. To not confound 2D retinal features and 3D structure, we held the retinotopic area constant for all stimuli [32, 38, 39].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has shown that the 3D orientation tuning of CIP neurons is largely invariant 25 to changes in the mean depth of the stimuli relative to the fixation plane, as well as the defining 26 visual (i.e., perspective or stereoscopic) cue, suggesting that CIP neurons are sensitive to depth 27 gradients (Taira et al, 2000;Tsutsui et al, 2001;Rosenberg and Angelaki, 2014b). In the present 28 study, we did not have sufficient stimulus conditions to determine whether the slant selectivity of 29 V3A neurons is also robust to changes in mean depth.…”
Section: Uncertain 24mentioning
confidence: 99%
“…The slant discrimination task was always performed along the 90Âş/270Âş tilt axis. To simplify 29 the description of surface orientation, we do not refer to tilt for the slant discrimination task but 30 instead denote planes with a tilt of 90Âş (top of the plane closer to the monkey) as having a negative 31 slant, and planes with a tilt of 270Âş (top of the plane further from the monkey) as having a positive 32 slant (c.f., Rosenberg and Angelaki, 2014b). As illustrated in Fig.…”
mentioning
confidence: 98%
“…Non-human primate fMRI studies have consistently shown strong activity in the parietal cortex during 3D perception in the presence disparities (Durand et al, 2007; Joly et al, 2009; Rosenberg et al, 2013; Rosenberg and Angelaki, 2014; Taira et al, 2000; Tsao et al, 2003; Tsutsui et al, 2002; Van Dromme et al, 2016, 2015; Verhoef et al, 2015). However, only a few fMRI studies (e.g., Chandrasekaran et al, 2007; Durand et al, 2009; Georgieva et al, 2009; Minini et al, 2010; Tsao et al, 2003) have examined the processing of 3D shape from binocular disparity in parietal cortex in humans.…”
Section: Introductionmentioning
confidence: 99%